A nitrogen and phosphorus co-doped carbon supported ruthenium-cobalt nanoparticle composite material, a preparation method therefor and an application thereof
Patent Information
- Application Number
- CN202411068662.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-06
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-08-06
AI Technical Summary
[0003]1、在第5次反应时的循环保持率仅为43.1%,即存在循环性能较差的问题;
[0053]1、使用改性碳材料作为一级载体:通过炭黑颗粒作为起始碳源,并掺杂N、P元素,成功引入缺陷,并且,改善了炭黑表面特性。此改性策略不仅增强了复合材料的稳定性,而且,提供了优异的电子传输能力,有利于活性物种的分散和催化反应的进行;
Smart Images

Figure CN118950060B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hydrogen production technology from ammonia borane hydrolysis in hydrogen storage materials, specifically to a nitrogen-phosphorus co-doped carbon-supported ruthenium-cobalt nanoparticle composite material, its preparation method, and its application. Background Technology
[0002] Ammonia-borane (NH3BH3), abbreviated as AB, has the characteristics of high hydrogen storage capacity, strong stability, and environmental friendliness. However, the hydrogen release kinetics of hydrolysis at room temperature is slow, requiring the use of catalysts to improve the reaction rate. Among the common solutions, Ru-based noble metal catalysts have the highest catalytic performance. However, such Ru-based noble metal catalysts generally suffer from metal agglomeration and high cost. Therefore, using carbon materials as a support to load Ru nanoparticles can effectively improve the dispersibility of Ru nanoparticles. For example, existing literature 1 (Liang H, Chen G, Desinan S, et al. In situ facile synthesis of ruthenium nanocluster catalyst supported on carbon black for hydrogen generation from the hydrolysis of ammonia-borane[J]. international journal of hydrogen energy, 2012, 37(23): 17921-17927.) prepared Ru nanoclusters Ru / C supported on carbon black through in-situ synthesis. The Ru nanoclusters were 1.7 nm in size, which indicates good dispersibility. At the same time, the Ru nanoclusters were stabilized and fixed by carbon black particles. A hydrogen evolution conversion rate of 429.5 mol% was achieved at 25°C in the catalytic hydrolysis of ammonia borane to produce hydrogen. H2 ·mol Ru -1 ·min -1 In addition to the technical effectiveness, the activation energy of this technical solution is 34.81±0.12kJ·mol⁻¹. -1 Compared with other existing technologies, this method exhibits better performance among reported Ru-based catalysts. However, it still has two technical problems:
[0003] 1. The cycle retention rate at the 5th reaction was only 43.1%, indicating poor cycle performance.
[0004] 2. Since this literature uses only a single noble metal, Ru, as the active metal, there is a problem of high catalyst cost.
[0005] To address the issue of poor catalyst stability, heteroatom-modified carbon materials can be used as supports for dispersing noble metals. For example, existing literature 2 (Zhong F, Wang Q, Xu C, et al. Ultrafine and highly dispersed Ru nanoparticles supported on nitrogen-doped carbon nanosheets: Efficient catalysts for ammonia borane hydrolysis[J]. Applied Surface Science, 2018, 455: 326-332.) prepared Ru / HPCM nanoparticles supported on nitrogen-doped hierarchical porous carbon materials (HPCM), where the Ru nanoparticles had a size of 1.41 nm. In the catalytic hydrolysis of ammonia borane to produce hydrogen, a hydrogen evolution conversion rate of 440 mol / L was achieved at 25 °C. H2 ·mol Ru -1 ·min -1 The technical effect is that it retains 50% of the initial catalytic activity after being reused 8 times. However, Ru / C catalysts prepared using this method still suffer from low cycling performance; after three cycles, the Ru / C catalyst retains only 46.7% of its initial catalytic activity. Although this technique demonstrates that doping with nitrogen can improve both catalyst stability and catalytic performance, the cycling performance of this technique does not meet application requirements.
[0006] For example, existing literature 3 (Zhong F, Wang Q, Xu C, et al. Catalytically active rhodium nanoparticles stabilized by nitrogen doped carbon for the hydrolysis of ammonia borane[J]. International Journal of Hydrogen Energy, 2018, 43(49): 22273-22280.) prepared Rh / NPC nanoparticles supported on nitrogen-doped carbon (NPC). A hydrogen evolution conversion rate of 473.5 mol / L was achieved at 25 °C in the catalytic hydrolysis of ammonia borane to produce hydrogen. H2 ·mol Ru -1 ·min -1The technical solution achieves significant improvements and can be reused up to eight times. The main reason for the enhanced performance is the large specific surface area and abundant nitrogen- and oxygen-containing functional groups of the NPC (nitrogen-doped carbon) catalyst. This characteristic effectively inhibits the aggregation of Rh nanoparticles, thereby enhancing the structural stability of the catalyst. This technical solution also demonstrates the positive effect of N-doped carbon materials on improving catalyst stability; however, it does not address the loading of Rh elements onto undoped carbon materials, meaning it cannot provide technical insights into the enhancement of Rh catalytic activity by N doping.
[0007] Furthermore, phosphorus-doped carbon materials can significantly improve the electron transfer efficiency between the support and the active metal, thereby enhancing catalytic activity. For example, existing literature 4 (Liu H, Xu C, Lu R, et al. Efficient hydrogenevolution from ammonia borane hydrolysis with Rh decorated on phosphorus-doped carbon[J]. International Journal of Hydrogen Energy, 2019, 44(31): 16548-16556.) successfully synthesized Rh nanoparticles in situ on porous phosphorus-functionalized carbon (PPC), thus preparing an Rh / PPC catalyst. A hydrogen evolution conversion rate of 806 mol / L was achieved at 25 °C in the catalytic hydrolysis of ammonia borane to produce hydrogen. H2 ·mol Ru -1 ·min -1 The technology achieves the desired effect, while also possessing a low activation energy of 22.7 kJ·mol⁻¹. -1 This technical solution demonstrates a synergistic effect between P-doped carbon materials and Rh. However, the cycling stability of this solution also fails to meet application requirements—the catalytic activity drops to 37% of the initial catalytic activity after four cycles. This is due to the aggregation of Rh nanoparticles.
[0008] Based on existing literature 3 and existing literature 4, the following conclusions can be drawn regarding supported catalysts using carbon materials as supports:
[0009] 1. Doping with nitrogen can significantly modulate the electronic structure of carbon materials, enhance their electronic conductivity, and effectively improve the structural stability of the materials;
[0010] 2. Doping with phosphorus introduces additional active sites, promotes electron transfer between active metal particles and the support, and further significantly enhances catalytic activity.
[0011] On the other hand, to optimize catalytic performance and reduce costs, composite catalysts can be prepared by combining transition metals with noble metals. In particular, introducing Co into transition metal catalyst systems can effectively improve hydrogen production rates. For example, existing literature 5 (Ye M, Wu J, Fan G. Hierarchical porous cobalt / carbon hybrid anchored Ru-catalyzed ammonia-borane hydrolysis for efficient H2 release[J]. Fuel, 2022, 321:123982.) prepared hierarchical porous nitrogen-doped carbon nanosheets (Co-NC) encapsulated with Co using a sodium chloride template method and anchored Ru nanoparticles (Ru@Co-NC). This achieved a hydrogen evolution conversion rate of 568 mol / L in the catalytic hydrolysis of ammonia-borane under neutral conditions at 25 °C. H2 ·mol Ru -1 ·min -1 Under alkaline conditions, it is 1131 mol. H2 ·mol Ru -1 ·min -1 The technical effect is that its performance is far superior to that of the comparative material Ru-NC (109min). -1 This technical solution confirms that Co and Ru have a synergistic catalytic effect in composite materials.
[0012] Building upon this, transition metal oxides, due to their unique electronic configuration and charge transport characteristics, can more effectively promote synergistic catalytic effects with noble metals compared to their ionic forms. For example, existing literature 6 (Prabu S, Vinu M, Chiang K Y. Ultrafine Ru nanoparticles in shape control hollow octahedron MOF derived cobalt oxide@carbon as high-efficiency catalysts for hydrolysis of ammonia borane[J]. Journal of the Taiwan Institute of Chemical Engineers, 2022, 139: 104511.) synthesized an irregular hollow octahedral core-shell structure with Co3O4 as the core and NC as the outer layer via a solvothermal reaction, and encapsulated Ru NPs (Ru@Co-O / NC). Among them, Ru@Co3O4 / NC-350 achieved a hydrogen evolution conversion rate of 883 min at 25℃ in the catalytic hydrolysis of ammonia borane.-1 The activation energy is 32.07 kJ·mol⁻¹ -1 The technical effect of this method is as follows: This solution uses Co3O4 as a support to achieve interaction with metallic Ru. While improving catalytic activity, it can maintain stable activity for the first four cycles. However, after 10 cycles, the activity retention rate is only 57%. This is because, although the method modifies the microstructure of the material, aiming to enhance catalytic activity by introducing defects or adjusting the form of Co, the resulting catalyst has a relatively large particle size of 1-2 μm. This significantly affects its specific surface area, the number of active sites, and particle dispersibility. Furthermore, the mass transfer resistance increases significantly with increasing particle size.
[0013] Based on existing literature 5 and 6, the following conclusions can be drawn regarding composite metal catalysts: In the same type of composite system, the form and valence state of the transition metal have a significant impact on its interaction with the active metal Ru; the defect structure and valence state changes of cobalt oxide can optimize its electronic structure and charge transport characteristics, thereby enhancing catalytic efficiency. However, the basic principles governing the catalytic effect of defects and multiple valence states in Co3O4 on the hydrolysis of ammonia borane have not yet been clearly defined in the existing literature.
[0014] Therefore, as the above analysis shows, the current technical problems can be solved by introducing multiple heteroatom co-doping to control the existence form and valence state of transition metal oxides. Simultaneously, the unique properties of heteroatoms can be used to adjust the defect structure of transition metal oxides. Specifically, the valence state of non-noble metals can be controlled by screening heteroatoms, and a support can be used to address the problem of large particle size and easy agglomeration of catalytic materials. Summary of the Invention
[0015] The purpose of this invention is to provide a nitrogen-phosphorus co-doped carbon-supported ruthenium-cobalt nanoparticle composite material, its preparation method, and its application.
[0016] The basic principle of this invention in solving the problems of the prior art is as follows: While employing a multi-stage support, nitrogen and phosphorus elements are used to regulate the defects in Co3O4, thereby enhancing the strong interaction between cobalt and ruthenium, ultimately improving catalytic activity. Specifically, the primary support mainly functions to regulate the defects in Co3O4; the secondary support mainly functions to improve the dispersion and stability of the noble metals.
[0017] To achieve the above-mentioned objectives, the technical solution adopted by this invention is as follows:
[0018] A nitrogen-phosphorus co-doped carbon-supported ruthenium-cobalt nanoparticle composite material, abbreviated as Ru-Co-O / NPC, is composed of nitrogen-phosphorus co-doped carbon NPC, cobalt tetroxide (Co3O4), and ruthenium nanoparticles (Ru); wherein,
[0019] The NPC is prepared by using carbon black, melamine, phytic acid, formaldehyde, and ammonia as raw materials, through hydrothermal reaction to achieve cross-linking and esterification reaction, and then through high-temperature calcination to achieve doping of N and P elements.
[0020] The Co3O4 is prepared by hydrothermal reaction of cobalt acetate tetrahydrate and then oxidation in air, and then loaded onto NPC in situ to obtain Co-O / NPC.
[0021] The Ru is prepared by in-situ reduction of ruthenium trichloride hydrate and then loaded onto Co-O / NPC to obtain Ru-Co-O / NPC.
[0022] The microscopic morphology of the NPC is that of an aggregate of spherical small particles;
[0023] The Co-O / NPC exhibits a microstructure of spherical small particle aggregates.
[0024] The Ru-Co-O / NPC exhibits a microscopic morphology of spherical small particle aggregates.
[0025] A method for preparing a nitrogen-phosphorus co-doped carbon-supported ruthenium-cobalt nanoparticle composite material includes the following steps:
[0026] Step 1, Preparation of NPC: First, melamine, carbon black, water, and formaldehyde are ultrasonically mixed under certain conditions, and then stirred under certain conditions to obtain solution A. Simultaneously, phytic acid, ammonia, and water are mixed to obtain solution B. Then, under certain conditions, solution B is added to solution A and mixed to obtain solution C. Next, solution C undergoes a hydrothermal reaction under certain conditions. After the reaction is complete, it is centrifuged, washed, and dried. Finally, under certain conditions, it is calcined at high temperature to achieve carbonization and doping, thus obtaining nitrogen-phosphorus co-doped carbon, named NPC.
[0027] In step 1, the conditions for preparing solution A are as follows: ultrasonic time of 5-10 min, stirring temperature of 60-80℃, and stirring time of 10-30 min; the ratio of melamine, carbon black, water, and formaldehyde is 0.5:0.2:32:4.
[0028] In step 1, the conditions for preparing solution B are that the ratio of phytic acid, ammonia, and water satisfies 4:5:16.
[0029] In step 1, the conditions for preparing solution C are: under magnetic stirring, the mixing temperature is 60-80℃;
[0030] In step 1, the hydrothermal reaction conditions are: hydrothermal temperature of 150-180℃ and hydrothermal time of 4-6h.
[0031] In step 1, the calcination conditions are as follows: under an argon atmosphere, the heating rate is 2-10℃·min. -1 The calcination temperature is 700-900℃, and the calcination time is 1-3 hours.
[0032] In step 1, the conditions for centrifugal washing are as follows: deionized water is used as the washing liquid, and the centrifugation speed is 6000-8000 r·min. -1 Centrifugation time is 3-5 minutes, and washing is performed 3-5 times.
[0033] In step 1, the drying conditions are: drying temperature of 60-80℃ and drying time of 8-12h.
[0034] Step 2, Preparation of Co-O / NPC: First, the NPC obtained in Step 1, cobalt acetate tetrahydrate, and urea are placed in an ethylene glycol solution and ultrasonically stirred to obtain solution D. Then, under certain conditions, solution D undergoes a hydrothermal reaction. After the reaction is complete, the solution is centrifuged, washed, and dried. Finally, calcination is performed to achieve oxidation, thus obtaining a nitrogen-phosphorus co-doped carbon-supported cobalt oxide composite material, named Co-O / NPC.
[0035] In step 2, the ratio of NPC, cobalt acetate tetrahydrate, urea and ethylene glycol solution satisfies 25:12:75:10.
[0036] In step 2, the hydrothermal reaction conditions are: hydrothermal temperature of 150-180℃ and hydrothermal time of 4-6h.
[0037] In step 2, the calcination conditions are as follows: under an air atmosphere, the temperature rises at a rate of 2-5°C / min. -1 The calcination temperature is 300-400℃, and the calcination time is 1-3 hours.
[0038] In step 2, the conditions for centrifugal washing and drying are the same as in step 1;
[0039] Step 3, Preparation of Ru-Co-O / NPC: First, under room temperature conditions, the Co-O / NPC obtained in Step 2 is placed in deionized water to obtain solution E. At the same time, ruthenium trichloride hydrate is placed in deionized water to obtain solution F. Then, under certain conditions, solution F is slowly added dropwise to solution E to obtain solution G. Finally, under certain conditions, solution G is first sonicated and then stirred. The resulting product is filtered, washed, and dried to obtain the nitrogen-phosphorus co-doped carbon-supported ruthenium-cobalt nanoparticle composite material, named Ru-Co-O / NPC.
[0040] In step 3, the mass ratio of Co-O / NPC to ruthenium trichloride hydrate is 20:3;
[0041] In step 3, the conditions for preparing solution G are as follows: under magnetic stirring, the conditions are: first, sonication, and then stirring, with the sonication time being 10-30 min and the stirring time being 18-24 h.
[0042] A nitrogen-phosphorus co-doped carbon-supported ruthenium-cobalt nanoparticle composite material, when used as a catalytic catalyst for hydrogen production via the hydrolysis of ammonia borane, exhibits a complete hydrogen release time of 20-40 seconds and a maximum hydrogen evolution conversion rate of 1300-1600 mol / L at 25°C. H2 ·mol Ru -1 ·min -1 The activation energy for catalytic hydrogen release is E. a =20-25kJ·mol -1 After 10 cycles, the catalyst retains 70-75% of its initial catalytic activity.
[0043] The beneficial technical effects of the material obtained by this invention can be seen from the following tests:
[0044] XRD analysis of this invention shows that Ru-Co-O / NPC contains only the characteristic peaks of graphite carbon. The test results indicate that it does not contain the characteristic peaks of Ru, N, P, or Co3O4, indicating that there is a highly disordered crystal structure.
[0045] According to EDS testing, Ru-Co-O / NPC contains not only C, N, P, O and Co elements, but also Ru element, and its distribution is relatively concentrated.
[0046] XPS analysis of this invention shows that N and P elements were successfully doped into the carbon matrix and the Co3O4 lattice, and that Co exists in multiple valence states.
[0047] SEM analysis revealed that Ru-Co-O / NPC exhibits a microstructure of spherical small particle aggregates.
[0048] TEM analysis revealed that Ru-Co-O / NPC exhibits a microstructure of spherical small particle aggregates.
[0049] Hydrogen production tests conducted according to this invention show that the complete hydrogen release time is 20-40 seconds, and the maximum hydrogen evolution conversion rate is 1300-1600 mol. H2 ·mol Ru -1 ·min -1 ;
[0050] The apparent activation energy E of the reaction was determined by reaction kinetics testing according to this invention. a =20-25kJ·mol -1 ;
[0051] According to the cyclic performance test of this invention, after 10 cycles at 25°C, the catalyst retains 70-75% of its initial catalytic activity.
[0052] Therefore, the present invention has the following advantages over the prior art:
[0053] 1. Using modified carbon materials as primary carriers: By using carbon black particles as the starting carbon source and doping with N and P elements, defects were successfully introduced, and the surface properties of the carbon black were improved. This modification strategy not only enhances the stability of the composite material but also provides excellent electron transport capabilities, which is beneficial for the dispersion of active species and the catalytic reaction.
[0054] 2. Utilizing the synergistic effect of nitrogen and phosphorus: Melamine was used as a nitrogen source and phytic acid as a phosphorus source. They were successfully doped into the carbon skeleton and cobalt tetroxide. This not only enhanced the interaction between the active species and the support, but also successfully regulated the electronic structure of the noble metal ruthenium, optimized the adsorption performance of the composite material, and promoted the catalytic reaction.
[0055] 3. Utilizing the synergistic effect of Ru and Co: Ru provides intrinsic sites with high catalytic activity, while the addition of Co significantly enhances the catalytic efficiency of Ru through a synergistic effect, which not only improves catalytic activity and stability, but also achieves effective control of catalyst cost.
[0056] 4. All raw materials used are industrially produced chemical raw materials that are readily available on the market. The preparation process is simple, the reaction conditions are mild, and the energy consumption and pollution are low.
[0057] 5. As a catalytic hydrogen production material, the nitrogen-phosphorus co-doped carbon-supported ruthenium-cobalt nanoparticle composite material has a high efficiency in catalyzing the hydrolysis of ammonia-borane to produce hydrogen. It has a high hydrogen evolution conversion rate at 25℃ and a low apparent activation energy of the reaction. Attached image description:
[0058] Figure 1 XRD patterns of NPC, Co-O / NPC, and Ru-Co-O / NPC prepared in Example 1;
[0059] Figure 2 The image shows the SEM image of the NPC prepared in step 1 of Example 1.
[0060] Figure 3 The image shows the SEM image of the Co-O / NPC prepared in step 2 of Example 1.
[0061] Figure 4 EDS image of Ru-Co-O / NPC prepared in step 3 of Example 1;
[0062] Figure 5 XPS image of Ru-Co-O / NPC prepared in step 3 of Example 1;
[0063] Figure 6 The image shows a SEM image of the Ru-Co-O / NPC prepared in step 3 of Example 1.
[0064] Figure 7 TEM image of Ru-Co-O / NPC prepared in step 2 of Example 1;
[0065] Figure 8 This is a high-resolution transmission electron microscope image of Ru-Co-O / NPC prepared in step 3 of Example 1;
[0066] Figure 9 The graph shows the hydrogen release curves of ammonia borane hydrolysis at 25°C for the Co-O / NPC prepared in step 2 and the Ru-Co-O / NPC prepared in step 3 in Example 1.
[0067] Figure 10 The graphs show the comparison curves and activation energy curves of Ru-Co-O / NPC catalytic hydrolysis of ammonia borane to produce hydrogen at different temperatures in Example 1.
[0068] Figure 11 The hydrogen evolution conversion rate and cycle retention rate of the Ru-Co-O / NPC catalytic hydrolysis of ammonia borane to produce hydrogen in Example 1 are obtained from 10 cycles.
[0069] Figure 12 This is a SEM image of the Ru-Co-O / NPC catalytic hydrolysis of ammonia borane to produce hydrogen after 10 cycles in Example 1;
[0070] Figure 13 The graphs show the hydrogen release curves of catalytic hydrolysis of ammonia borane in Example 1 and Comparative Examples 1, 2, and 3 at 25°C.
[0071] Figure 14The hydrogen conversion rate of catalytic hydrolysis of ammonia borane in Example 1 and Comparative Examples 1, 2 and 3 at 25°C;
[0072] Figure 15 The graphs show the hydrogen release curves of catalytic hydrolysis of ammonia borane in Examples 1 and 2, Comparative Examples 4 and 5 at 25°C.
[0073] Figure 16 The hydrogen conversion rates of catalytic hydrolysis of ammonia borane in Examples 1 and 2, Comparative Examples 4 and 5 at 25°C are shown.
[0074] Figure 17 The graphs show the hydrogen release curves of catalytic hydrolysis of ammonia borane in Example 1, Comparative Examples 6 and 7 at 25°C.
[0075] Figure 18 The hydrogen conversion rate of catalytic hydrolysis of ammonia borane in Example 1, Comparative Examples 6 and 7 at 25°C is shown. Detailed Implementation
[0076] The present invention will be further described in detail through Embodiment 1, in conjunction with the accompanying drawings, but this is not intended to limit the scope of the invention.
[0077] Example 1
[0078] A method for preparing a nitrogen-phosphorus co-doped carbon-supported ruthenium-cobalt nanoparticle composite material includes the following steps:
[0079] Step 1, Preparation of NPC: First, 0.5g melamine, 0.2g carbon black, 32mL water, and 4mL formaldehyde were ultrasonically mixed for 10min. Then, the mixture was stirred at 70℃ for 10min to obtain solution A. Simultaneously, 2mL phytic acid, 2.5mL ammonia, and 8mL water were mixed to obtain solution B. Then, under magnetic stirring at 70℃, solution B was added to solution A to obtain solution C. Next, solution C underwent a hydrothermal reaction at 160℃ for 4h. After the reaction was complete, the solution was centrifuged, washed, and dried. Finally, under an argon atmosphere, the mixture was heated at a rate of 5℃·min. -1 Under the conditions of calcination temperature of 750℃ and calcination time of 90min, high-temperature calcination is carried out to achieve carbonization and doping, and nitrogen-phosphorus co-doped carbon can be obtained, named NPC;
[0080] In step 1, the conditions for centrifugal washing are as follows: deionized water is used as the washing liquid, and the centrifugation speed is 8000 r·min. -1 The centrifugation time was 3 minutes, and the washing was performed 3 times.
[0081] In step 1, the drying conditions are: drying temperature of 60℃ and drying time of 10h.
[0082] To verify the phase composition of the NPC obtained in step 1, XRD tests were performed. The XRD test results are as follows: Figure 1 As shown, NPC contains characteristic peaks of graphitic carbon but not characteristic peaks of nitrogen (N) and phosphorus (P). The test results indicate that carbon (C) in NPC exists in a graphitic structure, while nitrogen (N) and phosphorus (P) exist in an amorphous state.
[0083] To verify the microstructure of the NPC obtained in step 1, SEM testing was performed. The test results are as follows: Figure 2 As shown, NPC is a carbon black particle in the form of a spherical aggregate of small particles, that is, a nanoparticle aggregate in which multiple primary particles are fused together as the basic structural unit.
[0084] Step 2, Preparation of Co-O / NPC: First, 75 mg of NPC obtained in Step 1, 25 mg of cobalt acetate tetrahydrate, and 12 mg of urea were placed in 10 mL of ethylene glycol solution and sonicated and stirred to obtain solution D. Then, solution D was subjected to a hydrothermal reaction at a hydrothermal temperature of 180 °C for 4 h. After the reaction was complete, the solution was centrifuged, washed, and dried. Finally, the solution was heated in air at a rate of 2 °C / min. -1 Under the conditions of calcination temperature of 350℃ and calcination time of 2h, oxidation is achieved by calcination, and nitrogen-phosphorus co-doped carbon-supported cobalt oxide composite material is obtained, named Co-O / NPC;
[0085] In step 2, the conditions for centrifugal washing and drying are the same as in step 1.
[0086] To verify the phase composition of the Co-O / NPC obtained in step 2, i.e., to demonstrate the effect of step 2 on the material composition, XRD tests were performed. The test results are as follows: Figure 1 As shown, in addition to the characteristic peaks of graphitic carbon, Co-O / NPC also exhibits characteristic peaks of Co3O4. The test results indicate that step 2 successfully loaded Co3O4 onto NPC. Furthermore, the relatively low diffraction intensity of the Co3O4 characteristic peaks suggests that N and P elements were doped into the Co3O4 lattice, modulating the surface state of the grains and leading to a decrease in diffraction intensity and a broadening of the diffraction peaks. Moreover, during step 2, the C element in NPC maintained its graphitic structure.
[0087] To verify the microstructure of the Co-O / NPC obtained in step 2, SEM testing was performed. The test results are as follows: Figure 3As shown, Co-O / NPC is an aggregate of spherical small particles. Comparison with the NPC obtained in step 1 shows that the basic morphology of Co-O / NPC is not significantly different from that of NPC, meaning that step 2 does not affect the microstructure of the material.
[0088] To compare the performance of the Ru-Co-O / NPC catalyst as a hydrogen production catalyst for the hydrolysis of ammonia borane, the Co-O / NPC obtained in step 2 was subjected to a hydrogen production test via the hydrolysis of ammonia borane, referred to as the hydrogen production test. The specific method for the hydrogen production test was as follows: Under standard atmospheric pressure and 25°C, 20 mg of the sample was placed in a wide-mouth bottle, and 20 mL of deionized water was added and stirred thoroughly to disperse the sample. Then, the wide-mouth bottle was connected to a water-filled metering tube in a constant-temperature water bath. Under magnetic stirring, 10 mL of a 0.1 mmol / mL ammonia borane aqueous solution was injected. Finally, the volume of hydrogen produced was calculated by the water displacement method; furthermore, the hydrogen evolution conversion rate was calculated by the hydrogen release time.
[0089] Hydrogen production test results of Co-O / NPC are as follows Figure 9 As shown, after a catalytic time of 400 s, the volume of hydrogen released was 5 mL. The test results indicate that the catalytic performance of Co-O / NPC is negligible.
[0090] Step 3, Preparation of Ru-Co-O / NPC: First, at room temperature, 20 mg of the Co-O / NPC obtained in Step 2 was placed in 10 mL of deionized water to obtain solution E. Simultaneously, 3 mg of ruthenium trichloride hydrate was placed in 10 mL of deionized water to obtain solution F. Then, under magnetic stirring, solution F was slowly added dropwise to solution E to obtain solution G. Finally, solution G was sonicated for 20 min and stirred for 20 h. The resulting product was filtered, washed, and dried to obtain the nitrogen-phosphorus co-doped carbon-supported ruthenium-cobalt nanoparticle composite material, named Ru-Co-O / NPC.
[0091] To verify the phase composition of the Ru-Co-O / NPC obtained in step 3, XRD analysis was performed. The test results are as follows: Figure 1 As shown, Ru-Co-O / NPC only contains the characteristic peaks of graphitic carbon and does not contain the characteristic peaks of Ru, N, P, or Co3O4. Comparing it with the Co-O / NPC obtained in step 2, it can be seen that in step 3, the C element in NPC still maintains the graphite structure.
[0092] Since XRD testing could not prove the presence of Ru, EDS testing was performed on Ru-Co-O / NPC. The test results are as follows. Figure 4As shown, Ru-Co-O / NPC contains C, N, P, O, and Co elements, as well as the Ru element. Test results show that step 3 successfully loads Ru.
[0093] Since XRD and EDS cannot prove the specific form of matter, XPS was performed to demonstrate the effect of Ru loading on Co3O4, the doping forms of N and P elements, and to prove the chemical state and surface electronic structure of Ru. The test results are as follows: Figure 5 As shown,
[0094] Ru exists in a zero-valence state, while the presence of a positive valence state is attributed to charge transfer induced by heteroatom doping and the possible unavoidable oxidation.
[0095] Co exists in multiple valence states because of the electronegativity differences between N, P and O elements. This phenomenon indicates that N and P elements regulate the chemical environment of Co3O4.
[0096] The presence of phosphorus (P) in the form of stable Co-P bonds indicates that P has been successfully doped into the Co3O4 lattice and forms CP bonds, meaning that P is embedded in the carbon matrix structure, thereby modifying the carbon matrix.
[0097] Nitrogen exists in pyridine, pyrrole, and graphitic forms, indicating that nitrogen has been successfully embedded within the carbon matrix structure, thereby modifying the carbon matrix.
[0098] To verify the microstructure of the Ru-Co-O / NPC obtained in step 3, SEM testing was performed. The test results are as follows: Figure 6 As shown, Ru-Co-O / NPC is an aggregate of spherical small particles. A comparison with the NPC obtained in step 1 and the Co-O / NPC obtained in step 2 reveals that the basic morphology of Ru-Co-O / NPC is not significantly different from that of NPC and Co-O / NPC, indicating that step 3 does not affect the microstructure of the material.
[0099] To further verify the morphological structure of the Ru-Co-O / NPC obtained in step 3, TEM testing was performed. The test results are as follows: Figure 7 As shown, Ru-Co-O / NPC is an aggregate of spherical small particles, and the spherical small particles are of uniform size.
[0100] The combined results of SEM and TEM tests show that Ru nanoparticles were successfully loaded onto the Co-O / NPC surface.
[0101] To further confirm the existence of Co3O4 and the doping forms of N and P elements, HRTEM tests were performed, and the resulting images were then subjected to FFT transformation. The test results are as follows: Figure 8 As shown,
[0102] lattice spacing is Corresponding to the (311) crystal plane of Co3O4;
[0103] lattice spacing is Corresponding to the (111) lattice plane of CoO;
[0104] lattice spacing is Corresponding to the (112) crystal plane of Co2P;
[0105] lattice spacing is Corresponding to the (211) crystal plane of CoP;
[0106] lattice spacing is Corresponding to the (111) crystal plane of Co2N;
[0107] lattice spacing is Corresponding to the (111) crystal plane of CoN;
[0108] lattice spacing is and These correspond to the (111) and (101) crystal planes of Ru, respectively.
[0109] The test results lead to the following conclusions:
[0110] 1. It was confirmed that N and P elements were successfully incorporated into Co3O4, thus successfully regulating the structure of Co3O4;
[0111] 2. It was confirmed that Ru exists in its metallic elemental form.
[0112] The combined results of the XPS and HRTEM tests demonstrate that:
[0113] 1. Ru-Co3O4 / NPC is composed of Ru, CoN, Co2N, CoP, Co2P, CoO, Co3O4 and amorphous carbon;
[0114] 2. The role of NPC in the technical solution is not only as a carrier material, but also to provide N and P elements, thereby enabling the adjustment of the Co3O4 structure;
[0115] 3. Due to the introduction of Ru, electron transfer occurs between Ru and Co3O4, resulting in Co3O4 existing in an amorphous state.
[0116] The hydrogen production test results of Ru-Co-O / NPC are as follows: Figure 9As shown, the time for complete hydrogen release was 38 seconds, and the maximum hydrogen evolution conversion rate was 1429.2 mol. H2 ·mol Ru -1 ·min -1 .
[0117] Compared with the Co-O / NPC obtained in step 2, it can be seen that the introduction of Ru can significantly improve the catalytic hydrogen production performance. This is because the Ru atom, as the active center, forms a synergistic effect with the Co-O / NPC, which improves the electron transport efficiency at the interface, thereby significantly improving the catalytic efficiency and selectivity of hydrogen release from ammonia borane hydrolysis.
[0118] Further comparison with existing literature 5 and existing literature 6 shows that the maximum hydrogen evolution conversion rate of the present invention is 2.5 times that of existing literature 5 and 1.6 times that of existing literature 6. That is, the test results show that the simultaneous doping of nitrogen and phosphorus elements can modify and finely control carbon materials and cobalt oxide, and at the same time, can produce a synergistic effect with Ru atoms to further improve the overall catalytic activity. In particular, the doping of P element plays a significant role in accelerating the hydrogen production process.
[0119] To demonstrate the effect of Ru-Co-O / NPC on the hydrolysis kinetics of ammonia borane, hydrogen production tests were conducted at different temperatures: 25℃, 30℃, 35℃, and 40℃. The test results are as follows: Figure 10 As shown in Table 1, the hydrogen desorption rate increases significantly with increasing temperature. The apparent activation energy of the Ru-Co-O / NPC reaction, fitted by the Arrhenius equation, is E. a =21.56 kJ·mol -1 The fitting results show that Ru-Co-O / NPC can significantly improve the kinetic performance of ammonia borane hydrolysis.
[0120] Table 1. Hydrogen evolution conversion rates of ammonia borane hydrolysis catalyzed by Ru-Co-O / NPC at different temperatures.
[0121] <![CDATA[hydrogen evolution conversion rate (mol H2 ·mol Ru -1 ·min -1 )]]> 1429.2 1602.1 1838.1 2171.0
[0122] In order to compare the technical effects with those of existing technologies, this invention is compared with existing literature. a The results are summarized in Table 2. A comparison with existing literature shows that this invention E... a It is 21.56 kJ·mol -1 The results are lower than those in existing literature, indicating that NPC, Co3O4 and Ru have synergistic catalysis, which can effectively reduce the reaction energy barrier and make the AB hydrolysis reaction easier to occur.
[0123] Table 2 Summary of performance comparison between Ru-Co-O / NPC and existing references
[0124]
[0125] To demonstrate the cycling performance of Ru-Co-O / NPC, a cycling performance test was conducted. The specific test method involved repeatedly injecting an aqueous solution of ammonia borane to perform hydrogen production tests, thus achieving the cycling performance test. The cycling performance test results of Ru-Co-O / NPC are as follows: Figure 11 As shown in Table 3, when the number of cycles is 5, the time for complete hydrogen release is 39 s, and the maximum hydrogen evolution conversion rate is 1303.5 mol. H2 ·mol Ru -1 ·min -1 The time for complete hydrogen release did not change significantly, and the retention rate of the maximum hydrogen evolution conversion rate was 91.2%.
[0126] When the number of cycles is 10, the time for complete hydrogen release is 51 seconds, and the maximum hydrogen evolution conversion rate is 1028.5 mol. H2 ·mol Ru -1 ·min -1 The time for complete hydrogen release increased significantly, and the retention rate of the maximum hydrogen evolution conversion rate was 72%.
[0127] Table 3 Summary of Ru-Co-O / NPC Cycle Retention Rate
[0128] Cycle retention rate / % 100 93.6 93.2 92.1 91.2 90.6 79.8 73.9 73.2 72.0
[0129] Table 2 shows a summary of the cycle retention rates of this invention and existing literature:
[0130] Further comparison with existing literature 4 shows that the retention rate of the present invention after 5 cycles is 91.2%, which is higher than that of existing literature 4. That is, the test results show that the doping of N element can effectively improve the adsorption capacity of carbon material, promote the anchoring and stabilization of active metal on the surface of carbon material, thereby enhancing the stability of the material.
[0131] Further comparison with existing literature 6 shows that the retention rate of the present invention after 10 cycles is 72%, which is higher than that of existing literature 6. That is, the test results show that using cobalt tetroxide supported on carbon with nitrogen and phosphorus elements as a support can enhance the interaction between the support and the active metal, and at the same time improve catalytic activity and stability.
[0132] To further demonstrate the cycling performance of Ru-Co-O / NPC, i.e., to prove the mechanism of improved cycling performance, SEM tests were performed on Ru-Co-O / NPC after 10 cycles. The test results are as follows: Figure 12 As shown, after 10 cycles, the basic morphology of Ru-Co-O / NPC shows no significant difference after the cycle, indicating that it is stable.
[0133] There are two reasons for the slight decrease in catalytic activity:
[0134] 1. The accumulation and coverage of reaction products on the surface of active sites hinders the effective contact between reactants and active sites;
[0135] 2. Slight aggregation occurs between active species, thereby reducing the number of effective active sites and the exposed area.
[0136] To demonstrate the effects of Co3O4 and N and P elements on the catalytic performance of Ru-Co-O / NPC, Comparative Example 1 is provided, which is a Ru / C composite material prepared by directly loading Ru element alone without introducing Co3O4, N elements and P elements.
[0137] Comparative Example 1
[0138] A method for preparing Ru / C composite material by directly loading Ru element alone. The steps not specifically described in the specific steps are the same as those in Example 1. The difference is that steps 1 and 2 are not required. In step 3, the carbon black in step 1 is used to replace Co-O / NPC, and Ru can be directly loaded on the carbon black. The resulting material is named Ru / C.
[0139] The hydrogen production test results of Ru / C are as follows: Figure 13 As shown, the time for complete hydrogen release is 245 s, and the hydrogen evolution conversion rate is as follows: Figure 14 As shown in Table 4, the maximum hydrogen evolution conversion rate is 200.3 mol. H2 ·mol Ru -1 ·min -1 .
[0140] Table 4. Hydrogen evolution conversion rates of ammonia borane hydrolysis catalyzed by Ru-based catalyst composites with different supports.
[0141]
[0142] Compared with the Ru-Co-O / NPC obtained in Example 1, it can be seen that the simultaneous introduction of Co3O4, N, and P elements can significantly improve the hydrogen desorption rate. The preliminary reason is that the simultaneous introduction of Co3O4, N, and P elements can regulate the electronic structure of the carbon material and the Co3O4 surface through N and P elements, while Co and Ru elements produce a synergistic effect.
[0143] To further demonstrate and confirm the combined effect of N and P elements on the catalytic performance of Ru-Co-O / NPC, Comparative Example 2 is provided, which prepares Ru-Co-O / C catalytic materials without the introduction of N and P elements.
[0144] Comparative Example 2
[0145] A method for preparing Ru-Co-O / C catalytic material without introducing N and P elements. The steps not specifically described in the details are the same as those in Example 1. The difference is that step 1 is not required. In step 2, the carbon black in step 1 is used to replace NPC, so that N and P elements are not introduced. Co3O4 and Ru elements are loaded on the carbon black. The resulting material is named Ru-Co-O / C.
[0146] The hydrogen production test results of Ru-Co-O / C are as follows: Figure 13 As shown, the time for complete hydrogen release is 121 seconds, and the hydrogen evolution conversion rate is as follows: Figure 14 As shown in Table 4, the maximum hydrogen evolution conversion rate is 411.2 mol. H2 ·mol Ru -1 ·min -1 .
[0147] Compared with the Ru / C obtained in Comparative Example 1, it can be seen that the introduction of Co-O alone can increase the maximum hydrogen evolution conversion rate by 105%. The reason is that Co-O has a unique electronic structure, which can transfer or share electrons with Ru metal, thereby changing the electron density and distribution on the Ru surface. In other words, it can produce a synergistic effect with Ru atoms and promote the improvement of catalytic efficiency.
[0148] Compared with the Ru-Co-O / NPC obtained in Example 1, it can be seen that the simultaneous introduction of N and P elements can reduce the chemical reaction energy barrier.
[0149] To further demonstrate and confirm the respective effects of N and P elements on the catalytic performance of Ru-Co-O / NPC, Comparative Example 3 is provided, in which Ru-Co-O / NC catalytic materials without the introduction of P element are prepared.
[0150] Comparative Example 3
[0151] A method for preparing Ru-Co-O / NC catalytic material without introducing P element is described. The steps not specifically described are the same as those in Example 1, except that in step 1, phytic acid amine solution is not added, so that P element is not introduced, and Co3O4 and Ru element are loaded on NC. The resulting material is named Ru-Co-O / NC.
[0152] The hydrogen production test results of Ru-Co-O / NC are as follows: Figure 13 As shown, the time for complete hydrogen release is 70 seconds, and the hydrogen evolution conversion rate is as follows: Figure 14 As shown in Table 4, the maximum hydrogen evolution conversion rate is 742.6 mol. H2 ·mol Ru -1 ·min -1.
[0153] Compared with the Ru-Co-O / NPC obtained in Comparative Example 2, it can be seen that doping with N element can enhance the electronic delocalization effect between the support and the particles, thereby effectively weakening the strength of BN bond and directly reducing the energy barrier of the rate-determining step in the catalytic hydrolysis of ammonia borane.
[0154] Compared with the Ru-Co-O / NPC obtained in Example 1, it can be seen that doping with P can regulate the electronic structure, promote the charge transfer from the metal center to the phosphorus element, thereby enhancing the catalyst's adsorption capacity for ammonia borane molecules and improving catalytic efficiency.
[0155] By comparing Comparative Examples 1, 2, and 3 with Example 1, the following conclusions can be drawn:
[0156] 1. Co-doping with nitrogen and phosphorus produces a synergistic effect, that is, N increases the active sites, while P regulates the electronic structure, resulting in better performance than single heteroatom doping.
[0157] 2. Simultaneous doping with nitrogen and phosphorus can regulate defects in Co3O4, thereby increasing active sites and further promoting catalytic reactions;
[0158] 3. By using a nitrogen and phosphorus co-doping strategy, the interaction between the active metal and the support is enhanced, while the dispersion and stability of the noble metal are optimized.
[0159] According to existing literature 5, there is no universal rule for the influence of the reaction environment on catalytic performance; that is, different types and structures of catalysts have different requirements for the reaction environment. Therefore, in order to demonstrate the influence of the alkaline reaction environment on the catalytic performance of Ru-Co-O / NPC of the present invention, Examples 2, 5, and 6 are provided, showing Ru-Co-O / NPC prepared under different alkaline reaction environments, i.e., different NaOH concentrations.
[0160] Example 2
[0161] A Ru-Co-O / NPC prepared with a NaOH concentration of 2 wt.% is prepared. The steps not specifically described in the details are the same as those in Example 1, except that in step 3, when preparing solution E, an additional 0.2 g of NaOH is added to achieve a NaOH concentration of 2 wt.%. The resulting material is named Ru-Co-O / NPC-2.
[0162] The hydrogen production test results of Ru-Co-O / NPC-2 are as follows: Figure 15 As shown, the time for complete hydrogen release is 28 seconds, and the hydrogen evolution conversion rate is as follows: Figure 16 As shown in Table 5, the maximum hydrogen evolution conversion rate is 1930.3 mol. H2 ·mol Ru-1 ·min -1 .
[0163] Table 5. Hydrogen evolution conversion rates of Ru-Co-O / NPC catalyzed ammonia borane hydrolysis under different NaOH concentrations.
[0164]
[0165] Compared with the Ru-Co-O / NPC obtained in Example 1, the maximum hydrogen evolution conversion rate was further increased to 135.1%;
[0166] Test results show that Ru-Co-O / NPC can be prepared under alkaline reaction conditions, which can significantly improve catalytic activity, that is, NaOH has an activating effect on Ru-Co-O / NPC.
[0167] Comparative Example 4
[0168] A Ru-Co-O / NPC prepared with a NaOH concentration of 1 wt.% is prepared. The steps not specifically described in the details are the same as those in Example 1, except that in step 3, when preparing solution E, an additional 0.1 g of NaOH is added to achieve a NaOH concentration of 1 wt.%. The resulting material is named Ru-Co-O / NPC-1.
[0169] The hydrogen production test results of Ru-Co-O / NPC-1 are as follows: Figure 15 As shown, the time for complete hydrogen release is 35 seconds, and the hydrogen evolution conversion rate is as follows: Figure 16 As shown in Table 5, the maximum hydrogen evolution conversion rate is 1535.6 mol. H2 ·mol Ru -1 ·min -1 .
[0170] Compared with the Ru-Co-O / NPC obtained in Example 1, it can be seen that although the maximum hydrogen evolution conversion rate is increased to 107.4%;
[0171] However, compared with the Ru-Co-O / NPC-2 obtained in Example 2, the maximum hydrogen evolution conversion rate decreased to 79.6%.
[0172] Test results show that when the NaOH concentration is too low, Ru-Co-O / NPC cannot be fully activated.
[0173] Comparative Example 5
[0174] A Ru-Co-O / NPC prepared with a NaOH concentration of 3 wt.% is prepared. The steps not specifically described in the details are the same as those in Example 1, except that in step 3, when preparing solution E, an additional 0.3 g of NaOH is added to achieve a NaOH concentration of 3 wt.%. The resulting material is named Ru-Co-O / NPC-3.
[0175] The hydrogen production test results of Ru-Co-O / NPC-3 are as follows: Figure 15 As shown, the time for complete hydrogen release is 47 seconds, and the hydrogen evolution conversion rate is as follows: Figure 16 As shown in Table 5, the maximum hydrogen evolution conversion rate is 1169.3 mol. H2 ·mol Ru -1 ·min -1 .
[0176] Compared with the Ru-Co-O / NPC obtained in Example 1, the maximum hydrogen evolution conversion rate decreased to 81.8%;
[0177] Compared with the Ru-Co-O / NPC-2 obtained in Example 2, the maximum hydrogen evolution conversion rate decreased to 60.6%.
[0178] Test results show that when the concentration of NaOH is too high, it not only fails to activate the catalyst, but also reduces the reaction rate of the original catalyst. This is because the competitive reaction increases, and the diffusion of reactants is hindered.
[0179] The following conclusions can be drawn from Example 2, Comparative Example 4, and Comparative Example 5:
[0180] The concentration of NaOH has a significant effect on the Ru-Co-O / NPC catalytic hydrolysis of ammonia borane:
[0181] 1. Within a certain range, the catalytic rate increases with the increase of sodium hydroxide concentration. This is because NaOH can regulate the surface chemical properties of the catalyst, that is, it has an activating effect.
[0182] 2. When the sodium hydroxide concentration is too high, the catalytic activity decreases. This is because too many hydroxide ions occupy active sites, leading to increased competition for reactions, which is not conducive to the mass transfer process.
[0183] To demonstrate the effect of the mass ratio of Co-O / NPC and ruthenium trichloride hydrate on the catalytic performance of Ru-Co-O / NPC, Comparative Examples 6 and 7 are provided.
[0184] Comparative Example 6
[0185] A Ru-Co-O / NPC with a mass ratio of Co-O / NPC to ruthenium trichloride hydrate of 10:3 is prepared. The steps are the same as those in Example 1 unless otherwise specified. The difference is that in step 3, the content of Co-O / NPC is adjusted to 10 mg when preparing solution E. The resulting material is named Ru-Co-O / NPC-a.
[0186] The hydrogen production test results of Ru-Co-O / NPC-a are as follows: Figure 17 As shown, the time for complete hydrogen release is 78 seconds, and the hydrogen evolution conversion rate is as follows: Figure 18 As shown in Table 6, the maximum hydrogen evolution conversion rate is 542.0 mol. H2 ·mol Ru -1 ·min -1 .
[0187] Table 6. Hydrogen evolution conversion rates of Ru-Co-O / NPC composite materials with different Co-O / NPC contents during the hydrolysis of ammonia borane.
[0188]
[0189] Compared with the Ru-Co-O / NPC obtained in Example 1, the maximum hydrogen evolution conversion rate decreased to 37.9%.
[0190] Test results show that when the amount of Co-O / NPC added is too small, the hydrogen evolution conversion rate decreases significantly. This is because Ru cannot be effectively dispersed, meaning the technical effect of Co-O / NPC cannot be fully realized.
[0191] Comparative Example 7
[0192] A Ru-Co-O / NPC with a mass ratio of Co-O / NPC to ruthenium trichloride hydrate of 10:1 was prepared. The steps not specifically described in the details are the same as those in Example 1, except that in step 3, the content of Co-O / NPC was adjusted to 30 mg when preparing solution E, and the resulting material was named Ru-Co-O / NPC-b.
[0193] The hydrogen production test results of Ru-Co-O / NPC-b are as follows: Figure 17 As shown, the time for complete hydrogen release is 38 seconds, and the hydrogen evolution conversion rate is as follows: Figure 18 As shown in Table 6, the maximum hydrogen evolution conversion rate is 1426.3 mol. H2 ·mol Ru -1 ·min -1 .
[0194] Compared with the Ru-Co-O / NPC obtained in Example 1, the maximum hydrogen evolution conversion rate decreased to 99.8%.
[0195] Test results show that when the amount of Co-O / NPC added is too large, the maximum hydrogen evolution conversion rate does not change significantly. This is because the dispersion of Ru on its surface has reached its optimization limit, and at the same time, the active sites that interact with Ru are saturated.
[0196] By comparing Comparative Examples 6 and 7 with Example 1, the following conclusions can be drawn:
[0197] 1. When the amount of Co-O / NPC added is too small, the active metal will overly cover the active sites of the support, thereby weakening the auxiliary catalytic function of the support material, resulting in a significant decrease in hydrogen evolution conversion rate.
[0198] 2. When the amount of Co-O / NPC added is too large, the synergistic effect between active sites is weakened due to the increased spacing between metal particles. Although a high reaction rate can be maintained, the hydrogen evolution conversion rate will not increase, and the cost of composite materials will increase.
Claims
1. A nitrogen-phosphorus co-doped carbon-supported ruthenium-cobalt nanoparticle composite material, characterized in that: The nitrogen-phosphorus co-doped carbon-supported ruthenium-cobalt nanoparticle composite material, abbreviated as Ru-Co-O / NPC, is composed of nitrogen-phosphorus co-doped carbon NPC, cobalt tetroxide (Co3O4), and ruthenium nanoparticles (Ru); among which, The NPC is prepared by using carbon black, melamine, phytic acid, formaldehyde, and ammonia as raw materials, through hydrothermal reaction to achieve cross-linking and esterification reaction, and then through high-temperature calcination to achieve doping of N and P elements. The Co3O4 is prepared by hydrothermal reaction of cobalt acetate tetrahydrate and then oxidation in air, and then loaded onto NPC in situ to obtain Co-O / NPC. The Ru is prepared by in-situ reduction of ruthenium trichloride hydrate and then loaded onto Co-O / NPC to obtain Ru-Co-O / NPC.
2. The nitrogen-phosphorus co-doped carbon-supported ruthenium-cobalt nanoparticle composite material according to claim 1, characterized in that: The microscopic morphology of the NPC is that of an aggregate of spherical small particles; The Co-O / NPC exhibits a microstructure of spherical small particle aggregates. The Ru-Co-O / NPC exhibits a microscopic morphology of spherical small particle aggregates.
3. The method for preparing the nitrogen-phosphorus co-doped carbon-supported ruthenium-cobalt nanoparticle composite material according to claim 1, characterized in that... Includes the following steps: Step 1, Preparation of NPC: First, melamine, carbon black, water, and formaldehyde are ultrasonically mixed under certain conditions, and then stirred under certain conditions to obtain solution A. Simultaneously, phytic acid, ammonia, and water are mixed to obtain solution B. Then, under certain conditions, solution B is added to solution A and mixed to obtain solution C. Next, solution C undergoes a hydrothermal reaction under certain conditions. After the reaction is complete, it is centrifuged, washed, and dried. Finally, under certain conditions, it is calcined at high temperature to achieve carbonization and doping, thus obtaining nitrogen-phosphorus co-doped carbon, named NPC. Step 2, Preparation of Co-O / NPC: First, the NPC obtained in Step 1, cobalt acetate tetrahydrate, and urea are placed in an ethylene glycol solution and ultrasonically stirred to obtain solution D. Then, under certain conditions, solution D undergoes a hydrothermal reaction. After the reaction is complete, the solution is centrifuged, washed, and dried. Finally, calcination is performed to achieve oxidation, thus obtaining a nitrogen-phosphorus co-doped carbon-supported cobalt oxide composite material, named Co-O / NPC. Step 3, Preparation of Ru-Co-O / NPC: First, under room temperature conditions, the Co-O / NPC obtained in Step 2 is placed in deionized water to obtain solution E. At the same time, ruthenium trichloride hydrate is placed in deionized water to obtain solution F. Then, under certain conditions, solution F is slowly added dropwise to solution E to obtain solution G. Finally, under certain conditions, solution G is first sonicated and then stirred. The resulting product is filtered, washed, and dried to obtain the nitrogen-phosphorus co-doped carbon-supported ruthenium-cobalt nanoparticle composite material, named Ru-Co-O / NPC. In step 3, the mass ratio of Co-O / NPC to ruthenium trichloride hydrate is 20:
3.
4. The preparation method according to claim 3, characterized in that: In step 1, the conditions for preparing solution A are as follows: ultrasonic time of 5-10 min, stirring temperature of 60-80 ℃, and stirring time of 10-30 min; the ratio of melamine, carbon black, water and formaldehyde satisfies 0.5:0.2:32:
4. In step 1, the conditions for preparing solution B are that the ratio of phytic acid, ammonia, and water satisfies 4:5:
16. In step 1, the conditions for preparing solution C are as follows: under magnetic stirring, the mixing temperature is 60-80℃.
5. The preparation method according to claim 3, characterized in that: In step 1, the hydrothermal reaction conditions are: hydrothermal temperature of 150-180 ℃ and hydrothermal time of 4-6 h. In step 1, the calcination conditions are as follows: under an argon atmosphere, the heating rate is 2-10 °C·min. -1 The calcination temperature is 700-900 ℃, and the calcination time is 1-3 h; In step 1, the conditions for centrifugal washing are as follows: deionized water is used as the washing liquid, and the centrifugation speed is 6000-8000 r·min. –1 Centrifugation time is 3-5 minutes, and washing is performed 3-5 times. In step 1, the drying conditions are: a drying temperature of 60-80 ℃ and a drying time of 8-12 h.
6. The preparation method according to claim 3, characterized in that: In step 2, the ratio of NPC, cobalt acetate tetrahydrate, urea and ethylene glycol solution satisfies 25:12:75:
10. In step 2, the hydrothermal reaction conditions are: hydrothermal temperature of 150-180℃ and hydrothermal time of 4-6 h. In step 2, the calcination conditions are as follows: under an air atmosphere, the temperature rises at a rate of 2-5 °C / min. -1 The calcination temperature is 300-400 ℃, and the calcination time is 1-3 h; In step 2, the conditions for centrifugal washing and drying are the same as in step 1.
7. The preparation method according to claim 3, characterized in that: In step 3, the conditions for preparing solution G are as follows: under magnetic stirring, the conditions are: first, sonication, and then stirring, with the sonication time being 10-30 min and the stirring time being 18-24 h.
8. The application of the nitrogen-phosphorus co-doped carbon-supported ruthenium-cobalt nanoparticle composite material according to claim 1 as a catalyst in the hydrolysis of ammonia borane to produce hydrogen, characterized in that: At 25 °C, the time for complete hydrogen release is 20-40 s, and the maximum hydrogen evolution conversion rate is 1300-1600 mol. H2 ·mol Ru –1 ·min –1 The activation energy for catalytic hydrogen release is E. a = 20-25 kJ·mol –1 .
9. The application of the nitrogen-phosphorus co-doped carbon-supported ruthenium-cobalt nanoparticle composite material according to claim 1 as a catalyst in the hydrolysis of ammonia borane to produce hydrogen, characterized in that: At 25 °C, after 10 cycles, the catalyst retains 70-75% of its initial catalytic activity.
Citation Information
Patent Citations
Ru-Co bimetallic nano supported catalyst for hydrolytic hydrogen release of ammonia borane and preparation method of Ru-Co bimetallic nano supported catalyst
CN107376996A
Cobalt-containing nitrogen-doped porous carbon-loaded ruthenium nanoparticle composite material as well as preparation method and application thereof
CN117920308A
